A literature review of cerium recovery from different aqueous solutions. Issue 1 (February 2021) - Allahkarami, Ebrahim; Rezai, Bahram
Abstract: The main goal of this review article is to provide recent progress regarding the separation and purification of cerium by different methods. The most commonly used methods for extracting and separating cerium from various solutions include precipitation, adsorption, and solvent extraction. Among them, solvent extraction (SX) is one of the popular techniques in hydrometallurgical processes for high purity cerium commercial production. The advantages of SX are including high capacity, ease of continuous operation, inexpensive setup, and the possibility of zero waste generation. Therefore, the separation and purification of cerium from various solutions using and related techniques will be reviewed in this paper (in more detail). Graphical Abstract: ga1 Highlights: The main sources of rare earth elements are bastnasite and monazite. The methods of recovering cerium from various solutions were studied. The performance of different adsorbents for the removal of cerium was evaluated. The effects of the operating parameters for the solvent extraction of cerium were investigated.